Characterization of antibiotic resistance genes in the species of the rumen microbiota - Yasmin Neves Vieira Sabino; Mateus Ferreira Santana; Linda Boniface Oyama; Fernanda Godoy Santos; Ana Júlia Silva Moreira; Sharon Ann Huws; Hilário Cuquetto Mantovani (Nature Communications, 2019)
Here, the authors combine in silico analysis of 435 genomes of ruminal bacteria and archaea with transcriptomics and in vitro assays to investigate the distribution, expression and mobility of antibiotic resistance genes within the ruminal microbiota, finding that the tet(W) gene is under positive selective pressure.